The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10060473
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Native Forests and Forest Plantations on Water Supply in Chile

Abstract: Over the past 40 years, south-central Chile has experienced important land-use-induced land cover changes, with massive conversion from native forests (NF) to Pinus radiata D.Don and Eucalyptus spp. exotic forest plantations (FP). Several case studies have related this conversion to a reduction in water supply within small catchments (<100 ha). In this work, we explore the impacts of NF and FP on streamflow by using a large-sample catchment dataset recently developed for Chile. We select 25 large forested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 35 publications
2
23
0
3
Order By: Relevance
“…Los bosques entregan múltiples beneficios además de secuestro de carbono, por lo que debieran ser el foco de los esfuerzos privados y públicos (Chazdon & Brancalion, 2019). La evidencia científica en Chile muestra que los bosques -si es que se les permite crecer-ayudan a regular los caudales, controlar la erosión y mantienen la biodiversidad (Alvarez-Garreton, Lara, Boisier & Galleguillos, 2019;Banfield, Braun, Barra, Castillo & Vogt, 2018;Braun et al, 2017;Iroumé, Mayen & Huber, 2006;Little, Lara, McPhee & Urrutia, 2009;C. Oyarzún, Campos & Huber, 1997;Oyarzún & Huber, 2003).…”
Section: Discussionunclassified
“…Los bosques entregan múltiples beneficios además de secuestro de carbono, por lo que debieran ser el foco de los esfuerzos privados y públicos (Chazdon & Brancalion, 2019). La evidencia científica en Chile muestra que los bosques -si es que se les permite crecer-ayudan a regular los caudales, controlar la erosión y mantienen la biodiversidad (Alvarez-Garreton, Lara, Boisier & Galleguillos, 2019;Banfield, Braun, Barra, Castillo & Vogt, 2018;Braun et al, 2017;Iroumé, Mayen & Huber, 2006;Little, Lara, McPhee & Urrutia, 2009;C. Oyarzún, Campos & Huber, 1997;Oyarzún & Huber, 2003).…”
Section: Discussionunclassified
“…The increase in the forest area was higher than 16% of the total basin area. Additionally, Alvarez-Garreton et al [78] demonstrated that annual runoff always decreases with the increase of forest plantation area. However, the magnitude of the changes depends on several factors, including the initial percentage of the land covered within the basin, the land use/cover type replacement, and the basin area and its type (dry or wet basins).…”
Section: Hydrological Response and Luccmentioning
confidence: 99%
“…Wehren et al 2010), and changes in land cover influence the distribution of streamflow, specifically baseflow volumes and flashiness of runoff (e.g. Vertessy 2000, Brown et al 2005, Alvarez-Garreton et al 2019. Consequently, providing information on such alterations is critical to assess the magnitude of human impacts on hydrological behaviour (e.g.…”
Section: The Extent Of Human Interventions Is Rarely Characterizedmentioning
confidence: 99%